IGF2BP1-mediated methylation of ABCA1 facilitates tumor progression by affecting cholesterol metabolism in lung adenocarcinoma - Shaohua Xu; Kai Liu; Zhao Chen; Weijian Tang; Zhoumiao Chen (Amino Acids)
Abstract ABCA1 is a key protein in maintaining cholesterol homeostasis, and its abnormal expression is associated with the progression of many cancers. Nonetheless, the specific molecular mechanisms by which ABCA1 facilitates the development of LUAD remain largely unexplored, necessitating further in-depth investigation. The TCGA-LUAD database was used to analyze the expression of ABCA1 in LUAD tissues. Subsequently, a cell model with overexpressed ABCA1 was constructed for verification through cell experiments. Cell function was evaluated using the Transwell assay and the colony formation assay. Intracellular cholesterol levels were detected using a kit. At the same time, the online database RM2 Target was employed to predict upstream factors that may have a methylation regulatory relationship with ABCA1. On this basis, Dot blot and MeRIP-qPCR techniques were employed to determine the degree of m6A modification. To clarify the mechanism of IGF2BP1 regulating ABCA1 through the m6A pathway, RNA pull-down binding experiments were carried out, and changes in mRNA stability were assessed using actinomycin D treatment. Finally, the biological function of the IGF2BP1/ABCA1 signaling axis during the growth and metastasis of LUAD in vivo was evaluated by establishing a xenograft animal model. Bioinformatics analysis and cell experimental results confirmed the low expression of ABCA1 in LUAD tissues and cells. ABCA1 significantly inhibited cell proliferation, migration, and invasion capabilities, promoted apoptosis, and reduced intracellular cholesterol levels. From a molecular perspective, IGF2BP1 recognized and bound to methylation sites on ABCA1 mRNA, thereby accelerating its degradation process, resulting in a substantial decrease in the stability of ABCA1 mRNA. Moreover, in vivo and in vitro experiments further confirmed that IGF2BP1 affected cholesterol metabolism by regulating the expression of ABCA1, thereby facilitating the malignant progression of LUAD. Overall, our research revealed that IGF2BP1 affects cholesterol metabolism by reducing the stability of ABCA1 mRNA through m6A modification, thereby boosting the malignant progression of LUAD and formulating a theoretical basis for subsequent LUAD treatment.